Synergistic effects of surfactant-assisted biodegradation of wheat straw and production of polysaccharides by Inonotus obliquus under submerged fermentation. (April 2019) - Xu, Xiangqun; Wu, Pan; Wang, Tianzhen; Yan, Lulu; Lin, Mengmeng; Chen, Cui
Graphical abstract: Highlights: Surfactant-assisted biodegradation of wheat straw by Inonotus obliquus under SmF. Ligninolytic enzymes change the chemical and surface structures of wheat straw. Surfactant-assisted fermentation is an efficient method for the lignocellulose bioconversion. Synergistic effects of the surfactant supplement and lignocellulose biodegradation. Enhanced production and antioxidant activity of the medicinal mushroom exo -polysaccharides. Abstract: Current work proposes an innovative wheat straw biomass utilization strategy that connects efficient lignocellulose biodegradation with exo -polysaccharide (EPS) production in I. obliquus under submerged fermentation. The addition of Tween 80 increased the activities of ligninolytic enzymes MnP, LiP and Lac by 1200%, 125% and 39.9%, respectively. When wheat straw lignin recalcitrance was substantially reduced with the aid of Tween 80, I. obliquus was capable of utilizing the substrates and in turn accumulated EPS. The degradation of cellulose, hemicellulose and lignin reached 46.1%, 46.4% and 44.1% on Day 9 of growth, respectively. Meanwhile, the maximum mycelial biomass and EPS production increased by 23.3% and 142.9%, respectively. The EPS had higher contents of sugar, protein, uronic acid, and mannose ratio, and higher antioxidant activity against 2, 2-diphenyl-1-picrylhydrazyl (DPPH), 2, 2-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS + ) and hydroxyl radicals.